Field-based approaches to characterizing long-term indoor environmental quality in homes - Purgiel, Andrew, author; Carter, Ellison, advisor; Blotevogel, Jens, committee member; Bond, Tami, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: indoor environmental quality; representativeness; weatherization; PM2.5; indoor air quality; variability